Distribution system reconfiguration for service restoration – part II : maximal restoration coverage method - Loh, Aik Hau (Nanyang Technological University, 2020)
The foundation of global distribution network infrastructures is based on principles of reliability that anchors on both sufficiency and security. Upholding this will empower distribution systems to function safely, resulting with minimal interruptions for consumers under normal operating conditions. However, the awareness of possible power grid outages due to unpredictable and unprecedented failures then led to the study of effective restoration strategies, in hopes of establishing highly resilient power systems worldwide. The resiliency of power system speaks of its ability to withstand, adjust, and promptly recover during a disruption. Hence, implementing these techniques would enhance overall situational awareness of the system and greatly reduce restoration time. The objective of this project is to achieve maximal restoration coverage through the means of distribution system reconfiguration. Self-adequate microgrids along with the dynamic changes after major blackouts occur will be investigated. The mathematical modelling of the various components, its constraints and variables that are in the system infrastructure will be studied as well. The implementation and its results will be simulated in python software and solved by commercial optimization solvers.